A role for cpeYZ in cyanobacterial phycoerythrin biosynthesis. - Kahn, K (1997)
Pigment mutant strain FdR1 of the filamentous cyanobacterium Fremyella diplosiphon is characterized by constitutive synthesis of the phycobiliprotein phycoerythrin due to insertional inactivation of the rcaC regulatory gene by endogenous transposon Tn5469. Whereas the parental strain Fd33 harbors five genomic copies of Tn5469, cells of strain FdR1 harbor six genomic copies of the element; the sixth copy in FdR1 is localized to the rcaC gene. Electroporation of FdR1 cells yielded secondary pigment mutant strains FdR1E1 and FdR1E4, which identically exhibited the FdR1 phenotype with significantly reduced levels of phycoerythrin. In both FdR1E1 and FdR1E4, a seventh genomic copy of Tn5469 was localized to the cpeY gene of the sequenced but phenotypically uncharacterized cpeYZ gene set. This gene set is located downstream of the cpeBA operon which encodes the alpha and beta subunits of phycoerythrin. Complementation experiments correlated cpeYZ activity to the phenotype of strains FdR1E1 and FdR1E4. The predicted CpeY and CpeZ proteins share significant sequence identity with the products of homologous cpeY and cpeZ genes reported for Pseudanabaena sp. strain PCC 7409 and Synechococcus sp. strain WH 8020, both of which synthesize phycoerythrin. The CpeY and CpeZ proteins belong to a family of structurally related cyanobacterial proteins that includes the subunits of the CpcE/CpcF phycocyanin alpha-subunit lyase of Synechococcus sp. strain PCC 7002 and the subunits of the PecE/PecF phycoerythrocyanin alpha-subunit lyase of Anabaena sp. strain PCC 7120. Phycobilisomes isolated from mutant strains FdR1E1 and FdR1E4 contained equal amounts of chromophorylated alpha and beta subunits of phycoerythrin at 46% of the levels of the parental strain FdR1. These results suggest that the cpeYZ gene products function in phycoerythrin synthesis, possibly as a lyase involved in the attachment of phycoerythrobilin to the alpha or beta subunit.